The Role of Imam AlJuwayni (DOB: 478AH/ 1085AD) in the Development of the Educational Movement in Nishapur - Janan Abdul-Kadhim Lazim (مجلة كلية التربية للبنات)
The research dealt with the personality of the scholar Al-Juwayni and his prominent role in enriching the scientific movement in Nishapur with various knowledge and sciences that he acquired in his life journey in education. He grew up in a well-known scientific family and received his education from famous scholars of his time. He had an effective role in the development of the scientific movement and its prosperity in the city due to his possession of various sciences in addition to the modern teaching methods that he followed in his teaching such as reading, discussion, and others. In addition to providing the Arab library with his various works in various types of sciences, including transmitted sciences such as jurisprudence, the principles of religion, and interpretation. The scholar was the focus of attention of students of knowledge and learning from all over the country, as they used to go to Nishapur in order to draw from his knowledge due to his wide fame in the Arab Islamic state in addition to his teaching methods.